Odpowiedzi

2010-04-14T18:09:31+02:00
Y=2t - 1 ; t
y+1=2t
t=y+1/2

v = at kwadrat/2 ; a
2v=at²
2v/a=t²
t=√2v/a

R = abc/4P ; P
R4P=abc
P=abc/4R

P = abx
x=P/ab

R = ax/b
Rb=ax
x=Rb/a

S = a/bx
Sbx=a
x=a/Sb

T = 1/abx
Tabx=1
x=1/Tab

y = 2t - 3x
y+3x=2t
3x=2t-y
x=2t-y/3

y = 2 (x-1)
y/2=x-1
x=y/2+1
Najlepsza Odpowiedź!
2010-04-14T18:17:57+02:00
Y=2t-1 |+1
y+1=2t |:2
t=½y+½

V=at²/2 |*2
2V=at² |:t²
a=2V:t²

R=abc:2P |*2P
R*2P=abc |:2R
P=abc/2R

P = abx |:ab
P/ab=x

R = ax/b |b
bR=ax |:a
bR/a=x

S = a/bx |*bx
Sbx=a |:Sb
x=a/Sb

T = 1/abx |*abx
Tabx=1 |:Tab
x=1/Tab

y = 2t - 3x |-2t
y-2t=-3x |:-3
y-2t/-3=x

y = 2 (x-1)
y=2x-2 |+2
y+2=2x |:2
y+2/2=x

1 5 1